“In vitro” Culture for “ex situ” Conservation of the Vulnerable Species “Moehringia Jank”e Griseb ex Janka - HOLOBIUC, Irina; CĂTANĂ, Rodica; MAXIMILIAN, Carmen; ANASTASIU, Paulina; CRISTEA, Victoria (Studia Universitatis Babeș-Bolyai Biologia, 2016)
Moehringia jankae Griseb. Ex Janka is an European endemite in the West area of Black Sea Region, being a Dobrogean element which can be found in the East side of Romania (in Hârşova, Moşu Hill, Macin National Park, between Greci and Macin, Consul Hill Reservation, Canaralele Hârşova, Topolog, Tuşan-Măgurele Hill, Cheia Jurassic Recife, Călugareni, Colţanii Mari Rocks) and also in Bulgaria. The purpose of our study was the evaluation of the natural populations, the identification of new populations in the distribution area and the elaboration of the ex situ preservation methodology based on biotechnological approach. Despite plant preservation is made usually in situ in the natural habitats, additionally ex situ measures can be useful in different situations, especially for vulnerable taxa, with reduced populations, with limited areas or problems with reproduction or seeds germination. In vitro collection establishment as ex situ preservation method is based on the elaboration of short and medium term cultures protocols, further long-term procedures can be also applied.